Comparing the effect of disinfection using some vegetable oils and sodium hypochlorite on others Mechanical and physical properties of heat-treated acrylic - اسماعيل مجد; مجد سلمان (Latakia University Journal -Medical Sciences Series, 2024)
Introduction: Disinfection of removable prosthetic dentures is essential for the success and continuity of these dentures, and the fact that the disinfection process prevents the patient carrying the removable prosthetic denture from contracting opportunistic mouth infections. The most prominent challenge in the home disinfection process for removable prosthetic dentures lies in using effective,biologically acceptable methods and have as little negative impact as possible on the structure and properties of the removable prosthetic denture. Objective: Present a new method for disinfecting removable prosthetic dentures and to study whether this new method ,which is the use of tested essential plant oils, has a less negative effect on removable prosthetic dentures than sodium hypochlorite, which is the most widely and traditional disinfectant used in this field. Materials and methods: The study sample included 160 samples of heat-treated acrylic resins in the shape of rectangular cuboids with dimensions 3*10*30 mm. They were divided into four main groups, and each main group was divided into four sub-groups (A, B, C, D), of which the groups (B, C, D) were immersed for a period of (one month, 3 months, 6 months) in order in each disinfection solution (cinnamon oil 3%, rosemary oil 3%, garlic oil 3%, sodium hypochlorite 0.5%) This was for 20 minutes daily, and after completing the immersion in the disinfectant solution, each group of samples was washed, dried, and kept in distilled water, while group /A/ was immersed in distilled water. At the end of each time period, the weight of each of the tested groups was measured, then a shear test was conducted for 5 samples from the group, and tensile test for the other five samples. Results: It was shown that the weight of the samples increased after immersion in all groups of solutions used as the immersion period increased, and the increase was the highest in group /D/. The highest increase was when using a sodium hypochlorite solution, followed by a rosemary solution, followed by a garlic oil solution, and finally when a cinnamon oil solution was used. . No statistically significant differences were observed between the average values of tensile forces and shear forces separately between the groups in the four solutions or between the time groups in each solution separately. Conclusions: There were no significant differences between the effect of immersion with the four solutions during the three time periods on the shear bond and tensile bond of the samples used. Tested solutions of essential plant oils can be used to disinfect removable prosthetic dentures.